Komposisi Jenis, Kelimpahan dan Indeks Ekologi Makro Alga di Perairan Desa Bandar Kabupaten Alor - Yanto Tell; Kaleb Kelendonu; Epenetus Malaibana; Sudarmiyanto Zainudin (Samakia : Jurnal Ilmu Perikanan, 2024)
The zoning status of Bandar village waters as a sustainable fishing zone allows for high anthropogenic activity. That will impact environmental changes and ecological pressures in the structure of the macroalgae community. Macroalgae have a high species composition and abundance in tropical waters, but these species are also very vulnerable to environmental changes and ecological pressures. Scientific publication search results show that there has not been scientific study about the species composition, abundance, and ecological index of macroalgae in the waters of Bandar village. On the other hand, scientific studies are very important to be carried out to support the increase in the effective management of Marine Protected Areas based on village, customs, and religion. This study was designed to know the species composition and abundance and macroalgae ecological indices through analysis of ecological indexes and community structure approaches. This research was conducted in June 2023 in the waters of Bandar village, Alor district. The results showed that there were 14 types of macroalgae from 3 classes which were found with a composition of 5 types of classes Rhodophyceae, 4 types of classes Phaeophyceae, and 5 types of classes Chlorophyceae. The total number of macroalgae found was 1081 individuals. The type of macroalgae most commonly found is the type Laurencia papillosa (479 individuals) while the least found was the species Jania sp (2 individuals). The value of the total abundance of macroalgae (KT) = 131.03 individual/m2. The highest abundance of macroalgae types is Laurencia papillosa with a value (K) = 58.06 individuals/m2, while the lowest of its kind Jania sp with a value (K) = 0.24 individuals/m2. The highest relative abundance of macroalgae of its kind is Laurencia papillosa with a value (KR) = 44.31% while the lowest of the type is Jania sp with a value (KR) = 0.19%. The index value of macroalgae diversity (H') is 1.587907 and is in the medium category (1 ≤ H' ≤ 3). The index value of macroalgae uniformity (E) is 0.62040 and is in the high category (E > 0.6). The macroalgae dominance index value (C) is 0.289170 and is included in the low category (0 < C ≤ 0.50). Overall, the environmental parameters and bottom substrate of Bandar village waters are suitable for the growth and development of macroalgae.